Internet connectivity disruption in Vietnam (Vietnam) - Voidly (2026)
CRITICAL severity mixed detected in Vietnam. Confidence: 75%. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: VN-2026-0081
Keywords: censorship; VN; mixed; critical